2019
DOI: 10.3389/fimmu.2019.01921
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Cannabinoids, Δ9- Tetrahydrocannabinol and Cannabidiol, Ameliorates Experimental Multiple Sclerosis by Suppressing Neuroinflammation Through Regulation of miRNA-Mediated Signaling Pathways

Abstract: Multiple sclerosis (MS) is a chronic and disabling disorder of the central nervous system (CNS) characterized by neuroinflammation leading to demyelination. Recently a combination of Δ9-tetrahydrocannabinol (THC) and Cannabidiol (CBD) extracted from Cannabis has been approved in many parts of the world to treat MS-related spasticity. THC+CBD combination was also shown to suppresses neuroinflammation, although the mechanisms remain to be further elucidated. In the current study, we demonstrate that THC+CBD comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 80 publications
(111 reference statements)
2
64
0
Order By: Relevance
“…A similar study carried out by Ma et al reported that microRNA-124 influences and controls the activity of TNF-α, TLR6, and MyD88 [150]. Moreover, they observed a reduction in NF-κB activity induced by microRNA-223, through the minimization of the expression of p65 phosphorylation [160]. Qi et al showed that microRNA-210, through its interaction with the p50 segment of NF-κB, reduces the expression of proinflammatory mediators induced by LPS [161].…”
Section: Micrornas Expression In Sepsis-induced By Cannabinoid Signalsupporting
confidence: 55%
“…A similar study carried out by Ma et al reported that microRNA-124 influences and controls the activity of TNF-α, TLR6, and MyD88 [150]. Moreover, they observed a reduction in NF-κB activity induced by microRNA-223, through the minimization of the expression of p65 phosphorylation [160]. Qi et al showed that microRNA-210, through its interaction with the p50 segment of NF-κB, reduces the expression of proinflammatory mediators induced by LPS [161].…”
Section: Micrornas Expression In Sepsis-induced By Cannabinoid Signalsupporting
confidence: 55%
“…It is speculated that the mixture of compounds in the cannabis oil extract used in these studies may have been more capable of eliciting a Th2 immune response than purified cannabidiol. In support of this, a mixture containing both cannabidiol and tetrahydrocannabinol promoted a Th2 and anti-inflammatory immune response in a murine experimental autoimmune encephalomyelitis model (Al-Ghezi et al 2019). It was noted that neither cannabidiol nor tetrahydrocannabinol alone was capable of eliciting the beneficial immune response.…”
Section: Comparisons With Other Studiesmentioning
confidence: 94%
“…These and other authors have been studying limonene effects in the context of its impacts in the CNS. For instance, limonene has shown to exhibit anxiolytic effect increasing hippocampal dopamine levels and serotonin in the prefrontal cortex [75]. Considering the information above exposed, this is just one of the many compounds to be still addressed in this review that are natural and abundant in different plants, which could be used as potential therapeutics for diseases dependent on the inflammatory and oxidative-stress processes.…”
Section: D-limonenementioning
confidence: 99%
“…We just established that phytocannabinoids demonstrate different pharmacological effects, and it can get even more intriguing and complex when we focus on previous data describing that the combined use of some phytocannabinoids can possibly increase the positive effects proportionate by them. For instance, the use of CBD associated with ∆9-THC promoted downregulation of the neuroinflammatory process in animal models of multiple sclerosis (MS) [75], besides, reducing pain [76] and muscle spasticity in MS patients [75]. Importantly, CBD attenuated the psychotropic effects of THC when used in a combined form [75].…”
Section: Cannabis Phytocannabinoids: Focus On Tetrahydrocannabinol Anmentioning
confidence: 99%
See 1 more Smart Citation